Reduced Insulin Signaling Targeted to Serotonergic Neurons but Not Other Neuronal Subtypes Extends Lifespan in Drosophila melanogaster - Dravecz, Nikolett; Shaw, Tommy; Davies, Isabella; Brown, Casey; Ormerod, Lewis; Vu, Gin; Walker, Tyler; Taank, Taran; Shirras, Alan D.; Broughton, Susan J. (Frontiers in Aging Neuroscience, 2022)
Reduced Insulin/IGF-like signaling (IIS) plays an evolutionarily conserved role in improving longevity and some measures of health-span in model organisms. Recent studies, however, have found a disconnection between lifespan extension and behavioral health-span. We have previously shown that reduction of IIS in Drosophila neurons extends female lifespan but does not improve negative geotaxis senescence and has a detrimental effect on exploratory walking senescence in both sexes. We hypothesize that individual neuronal subtypes respond differently to IIS changes, thus the behavioral outcomes of pan-neuronal IIS reduction are the balance of positive, negative and neutral functional effects. In order to further understand how reduced IIS in neurons independently modulates lifespan and locomotor behavioral senescence we expressed a dominant negative Insulin receptor transgene selectively in individual neuronal subtypes and measured the effects on lifespan and two measures of locomotor senescence, negative geotaxis and exploratory walking. IIS reduction in cholinergic, GABAergic, dopaminergic, glutamatergic, and octopaminergic neurons was found to have either no affect or a detrimental effect on lifespan and locomotor senescence. However, reduction of IIS selectively in serotonergic neurons resulted in extension of lifespan in females with no effect on locomotor senescence. These data indicate that individual neuronal subtypes respond differently to IIS changes in the modulation of lifespan and locomotor senescence, and identify a specific role for the insulin receptor in serotonergic neurons in the modulation of lifespan.